2008
DOI: 10.1124/jpet.107.135681
|View full text |Cite
|
Sign up to set email alerts
|

Nebivolol, but Not Metoprolol, Improves Endothelial Function of the Corpus Cavernosum in Apolipoprotein E-Knockout Mice

Abstract: To determine the effects and underlying mechanisms of treatment with the ␤-receptor blockers nebivolol and metoprolol on penile endothelial function in apolipoprotein E (ApoE) Ϫ/Ϫ mice, wild-type (WT) and ApoE Ϫ/Ϫ mice were fed with a cholesterolrich diet for 7 weeks. ApoE Ϫ/Ϫ mice were treated with nebivolol (10 mg/kg/day) or metoprolol (90 mg/kg/day). Endothelial function of aortic and corpora cavernosal tissue was assessed by pharmacological stimulation with carbachol (endothelium dependent) or glycerol tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 32 publications
(37 reference statements)
0
27
0
2
Order By: Relevance
“…Published mouse studies use metoprolol dosages of 20 to 165 mg/kg body weight/ day (Bartholomeu et al 2008;Baumhakel et al 2008;Sorrentino et al 2011). The recommended human dosage is 1.25 to 5.63 mg/kg body weight/day.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Published mouse studies use metoprolol dosages of 20 to 165 mg/kg body weight/ day (Bartholomeu et al 2008;Baumhakel et al 2008;Sorrentino et al 2011). The recommended human dosage is 1.25 to 5.63 mg/kg body weight/day.…”
Section: Discussionmentioning
confidence: 99%
“…Nebivolol (Neb) had no effect. b Metoprolol treatment significantly increased PKA levels in brain relative to control nebivolol dosages of from 1 to 10 mg/kg body weight/ day (Baumhakel et al 2008;Sacco et al 2011;Sorrentino et al 2011). The recommended human dose is from 63 to 500 μg/kg body weight/day.…”
Section: Discussionmentioning
confidence: 99%
“…The dosage was chosen on the basis of literature data (Asai et al 1999, Baumhäkel et al 2008. In previous experiments, we found that cardiac functional changes in response to the infusion of isoprenaline, a b-AR agonist, at the dose of 30 ng/kg per min did not occur in metoprolol-treated mice (Musumeci et al 2011).…”
Section: Chronic Administration Of Metoprololmentioning
confidence: 99%
“…Finally, to verify whether there is a direct link between b1-Ar signaling and the expression of b-Mhc, a selective b1-Ar antagonist metoprolol was administered to adult mice, at a dose of 100 mg/kg per day for 14 consecutive days (Asai et al 1999, Baumhäkel et al 2008. As shown in Fig.…”
Section: Metoprolol Increases B-mhc Expression In Male Micementioning
confidence: 99%
“…Likewise, nebivolol use was associated with a significant decrease of superoxide anion production via lipid peroxidation, whereas metoprolol failed to exert such beneficial effects [44].…”
Section: Nebivolol Versus the Other Beta Blockers In Hypertensive Patmentioning
confidence: 99%